Baicalein ameliorates cerebral ischemia-reperfusion injury by inhibiting ferroptosis via regulating GPX4/ACSL4/ACSL3 axis. (1st October 2022) - Li, Ming; Meng, Zhaoli; Yu, Shichao; Li, Jiarui; Wang, Yupeng; Yang, Wei; Wu, Hui
Abstract: Accumulating evidence have indicated that ferroptosis plays a crucial role in cerebral ischemia-reperfusion (I/R) injury which is the most serious treatment complication of ischemic stroke. Baicalein (5, 6, 7-trihydroxyflavone) is a main bioactive ingredient isolated from a traditional Chinese medicine named Baikal Skullcap, which is the root of Scutellaria baicalensis Georgi . This study investigated the potential role of baicalein in cerebral I/R injury using oxygen-glucose deprivation and reoxygenation (OGD/R) HT22 cells, transient middle cerebral artery occlusion (tMCAO) mice and RSL3-sitmulated HT22 cells. Baicalein improved the viability of OGD/R cells and significantly ameliorated cerebral I/R injury in tMCAO mice. Baicalein decreased the iron levels, lipid peroxidation production and morphology features of ferroptosis of the brain tissues in tMCAO mice, which indicated that baicalein ameliorated cerebral I/R injury by inhibiting ferroptosis in vivo and in vitro. We further confirmed that baicalein had the activity of inhibiting ferroptosis in RSL3-stimulated HT22 cells. Western blot revealed that baicalein inhibited the ferroptosis by regulating on the expression levels of GPX4, ACSL4 and ACSL3 in OGD/R cells, tMCAO mice and RSL3-stimulated HT22 cells. Our findings demonstrated that baicalein reversed the cerebral I/R injury via anti-ferroptosis, which was regulated by GPX4/ACSL4/ACSL3 axis. The results suggested that baicalein has therapeutic potential as a drug for cerebral I/R injury. Highlights: Validation the therapeutic potential of baicalein on cerebral I/R injury. Anti-cerebral I/R injury of baicalein partly regulated by inhibiting ferroptosis. Baicalein inhibits the ferroptosis in cerebral I/R injury via GPX4/ACSL3/ACSL4.